SUSTAINABLE AGRICULTURE OF MARKETING OF AGRICULTURE PRODUCT IN RURAL AREAS - Irmayani Irmayani; Yusriadi Yusriadi; Amirah Amrawaty; Rahmadani Rahmadani (International Journal of Economics Management and Social Science, 2018)
This study aims to explain the concept of coffee cultivation in the rural farming community in Enrekang District on coffee commodity farming. This farming community is able to survive in the coffee production competition by tidying up local values ​​that are considered important in its cultivation business. The principle of trust is packaged both in spiritual meaning that someone takes action against something because there is a meaning behind the action. The meaning behind the action is to build good relations with sellers and buyers so that both are closely connected because trust has been built on a solid foundation as a value that has been internalized well in his soul. The research method with symbolic interactionism approach in qualitative research explains that researchers as actors in this research must go directly to the field to see and be directly involved both witnessing speech, behavior, farming style and respondent's gesture so that data can be obtained in the field. The results of the study show that the local value that is inherent in the lives of farmers in this area is applying the principle of trust in the act of marketing agricultural products.